Veterinary Drugs Found in Pharmacies in Turkey (International Journal of Scientific Research and Management (IJSRM), 2019)
In this study veterinary drugs in RxMediapharma ® 2017 which actively used in pharmacies in Turkey were scanned. These veterinary drugs offered for sale in pharmacies are given active substances, animals used, drug form, route of application, local or imported. According to this result, Ministry of Health Licensed 1; Ministry of Food, Agriculture and Livestock Licensed 56 local and 23 imported and a total of 79 veterinary drugs were detected. In addition, when the Ministry of Food, Agriculture and Livestock Licensed drugs are grouped according to their pharmacological effects, it is determined that the licensed drug group which has the highest number with 43.75% is antibiotics. Although there are various studies concerning veterinary drug, İt is given as Turkey-scale all of these drugs has not been observed in an article expect e-data, and the data collected electronically, has been submitted to any scientific community. For this reason, it is thought that this study, which compiles veterinary drugs emphasizing therapeutic potential, will form the basis for future research.